Electrochemical assessment of some titanium and stainless steel implant dental alloys (2003)
ABSTRACT: Commercially pure titanium alloy, Ti--6A1'4V alloy and stainless steel screw implants were evaluated in both Ringer and synthetic saliva physiological solutions at body temperature by EIS (Electrochemical Impedance Spectroscopy) with immersion times of 30 d. Results were simulated as a "sandwich system" composed by four capacitors-resistances connected in series with the solution resistance. A model explaining the results in terms of the porosity and thickness of four different layers, was proposed.